Pengaruh Terpaan Media Internet dan Pola Pergaulan terhadap Karakter Peserta Didik - Ihsan, Masykur (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2016)
This research article found three conclusions as follows: First, the internet exposure negatively affect the character of the students MTs Muhammadiyah Majenang. The higher the internet exposure, then the character is not good learners. This conclusion was obtained through the correlation between media exposure variable internet (Variable X1) and variable character of learners (Variable Y), in which the figures obtained Pearson Product Moment correlation coefficient of -0.507 (strong negative correlation). Figures -0.507 correlation coefficient was significant at the 0.05 level of significance. Second, intercommunication patterns significantly influence the character of the students MTs Muhammadiyah Majenang. The more stringent rules of the association, the better the character of the students. conversely the free association of learners, their character is getting no better. This conclusion was obtained through Pearson Product Moment correlation test between variables X2 (social patterns) with a variable Y (character learners) in which the figures obtained correlation coefficient of 0.737 (very strong influence). Figures 0.737 correlation coefficient is significant at 0.05 level of significance. Third, the internet exposure and intercommunication patterns together a significant effect on the character of the students MTs Muhammadiyah Majenang. This conclusion was obtained through multiple regression test between internet exposure variable and intercommunication patterns variable with student character variable in which the figures obtained multiple correlation coefficient of 0.752 (included in the category of very strong).